Antireflux surgery and risk of lung cancer by histological type in a multinational cohort study. (October 2020) - Yanes, Manar; Santoni, Giola; Maret-Ouda, John; Ness-Jensen, Eivind; Färkkilä, Martti; Lynge, Elsebeth; Nwaru, Bright; Pukkala, Eero; Romundstad, Pål; Tryggvadóttir, Laufey; von Euler-Chelpin, My; Lagergren, Jesper
Abstract: Introduction: Airway micro-aspiration might contribute to the proposed associations between gastroesophageal reflux disease (GERD) and some lung diseases, including lung cancer. This study aimed to examine the hypothesis that antireflux surgery decreases the risk of small cell carcinoma, squamous cell carcinoma and adenocarcinoma of the lung differently depending on their location in relation to micro-aspiration. Methods: Population-based cohort study including patients having undergone antireflux surgery during 1980–2014 in Denmark, Finland, Iceland, Norway or Sweden. Patients having undergone antireflux surgery were compared with two groups: 1) the corresponding background population, by calculating standardised incidence ratios (SIRs) with 95% confidence intervals (CIs) and 2) non-operated GERD-patients, by calculating hazard ratios (HRs) with 95% CIs using multivariable Cox regression with adjustment for sex, age, calendar period, country, chronic obstructive pulmonary disease and obesity diagnosis or type 2 diabetes. Results: Among all 812, 617 GERD-patients, 46, 996 (5.8%) had undergone antireflux surgery. The SIRs were statistically significantly decreased for small cell carcinoma (SIR = 0.57, 95% CI 0.41–0.77) and squamous cell carcinoma (SIR = 0.75, 95% CI 0.60–0.92), but not for adenocarcinoma of the lung (SIR = 0.90, 95% CI 0.76–1.06). The HRs were also below unity for small cell carcinoma (HR = 0.63, 95% CI 0.44–0.90) and squamous cell carcinoma (HR = 0.80, 95% CI 0.62–1.03), but not for adenocarcinoma of the lung (HR = 1.03, 95% CI 0.84–1.26). Analyses restricted to patients with objective GERD (reflux oesophagitis or Barrett's oesophagus) showed similar results. Conclusions: This all-Nordic study indicates that patients who undergo antireflux surgery are at decreased risk of small cell carcinoma and squamous cell carcinoma of the lung, but not of adenocarcinoma of the lung. Highlights: Among 812, 617 patients with gastroesophageal reflux disease from the Nordic countries, 46, 996 had undergone antireflux surgery. Antireflux surgery decreased the risk of lung small cell carcinoma and squamous cell carcinoma. Antireflux surgery did not decrease the risk of lung adenocarcinoma. Analyses in patients with reflux oesophagitis or Barrett's oesophagus showed similar results.